2016
DOI: 10.18869/acadpub.pbr.2.2.58
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the bioadhesivity of Acconon MC 8-2 EP/NF for gastroretention of floating microsponges of loratadine and achieving controlled drug delivery

Abstract: Loratadine, a BCS class II drug is an oral H1 antihistaminic agent which exhibits poor water solubility and consequently poor dissolution. Loratadine is absorbed in the proximal part of the gastrointestinal tract (GIT); is stable in acidic pH, has a narrow therapeutic absorption window in the GIT and the presence of food enhances its bioavailability (1). The drug is available as tablets, oral suspension, syrup and quickdissolving tablets. All these dosage forms are challenged by hepatic first pass metabolism t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Optimisation by QBD for preparing microparticulate systems is nowadays practised by formulation scientists, and optimised operating variables aid in scale-up design. To enhance reliability and reproducibility of the method, several investigators started attempting simple factorial design [29], Central Composite Design -RSM method by design expert software [1,11,13,16,[28][29][30][31]. They presented linear as well as quadratic models.…”
Section: Introductionmentioning
confidence: 99%
“…Optimisation by QBD for preparing microparticulate systems is nowadays practised by formulation scientists, and optimised operating variables aid in scale-up design. To enhance reliability and reproducibility of the method, several investigators started attempting simple factorial design [29], Central Composite Design -RSM method by design expert software [1,11,13,16,[28][29][30][31]. They presented linear as well as quadratic models.…”
Section: Introductionmentioning
confidence: 99%
“…The gastric floating microsponge of curcumin developed using the two polymers eudragit and ethylcellulose together by Arya et al demonstrated a drug release of 88.4 to 90.8% of curcumin after 8 hours of the release study [26]. In another study reported by Singh et al, the cumulative drug release values obtained for the loratadine gastric floating microsponge prepared using ethylcellulose alone were comparatively slightly lower numbers 66.75 to 88.15% drug release [27] and in one more study, it is reported that cinnarizine release from the gastric floating microsponge was far less and it was between 57.9 and 88.7% at the end of same 8 hours [28]. However, on increasing the duration of the in vitro drug release study from 8 to 12 hours and with the use of both the polymers eudragit and ethylcellulose together in the microsponge preparation it was noticed that the drug release was almost complete as reported by Chargonda et al [29].…”
Section: Critical Factors Affecting Microsponge and Microsphere Efficacymentioning
confidence: 99%
“…Zero-order release was the best fit kinetic model for the microsponges developed with anyone polymer ethylcellulose or eudragit and dichloromethane alone as a solvent [29]. It is thus clear that the variation in the drugs release from the floating microsponges of curcumin [26], cinnarizine [28], famotidine [29], and loratadine [27] are related to the polymeric and solvent composition of each type of gastric floating microsponges. As far as the release mechanisms are concerned, all floating microsponges exhibited drug release governed by Fickian diffusion mechanisms [26,27], except to lower concentration of eudragit and it was governed by diffusion and swelling mechanisms [27].…”
Section: Critical Factors Affecting Microsponge and Microsphere Efficacymentioning
confidence: 99%
“…When compared to the aqueous medium the system offers lower bulk density that helps the drug de-livery system to float in the gastric fluid. Several approaches like mucoadhesive system, swelling system, high density system, magnetic system and floating system have been developed to increase the residence time of drug in stomach [7][8][9].…”
Section: Introductionmentioning
confidence: 99%